2012
DOI: 10.1002/cbic.201200396
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Differential Affinity of Small Molecules for Noncanonical DNA Structures

Abstract: The targeting of higher-order DNA structures has been thoroughly developed with G-quadruplex DNA but not with other structures like branched DNA (also known as DNA junctions). Because these alternative higher-order DNA architectures might be of high biological relevance, we implemented a high-throughput version of the FRET melting assay that enabled us to map the interactions of a candidate with four different DNA structures (duplex- and quadruplex DNA, three- and four-way junctions) in a rapid and reliable ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 92 publications
1
62
0
Order By: Relevance
“…23 Briefly, the stability of the DNA junction is evaluated through its thermal unfolding readily monitored via a modification of the fluorescence resonance energy transfer (FRET) relationship that occurs between fam and tamra probes present at both ends of the sequence. 23 Briefly, the stability of the DNA junction is evaluated through its thermal unfolding readily monitored via a modification of the fluorescence resonance energy transfer (FRET) relationship that occurs between fam and tamra probes present at both ends of the sequence.…”
Section: Dna Junction Interacting Properties Of Cationic Azacryptandsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Briefly, the stability of the DNA junction is evaluated through its thermal unfolding readily monitored via a modification of the fluorescence resonance energy transfer (FRET) relationship that occurs between fam and tamra probes present at both ends of the sequence. 23 Briefly, the stability of the DNA junction is evaluated through its thermal unfolding readily monitored via a modification of the fluorescence resonance energy transfer (FRET) relationship that occurs between fam and tamra probes present at both ends of the sequence.…”
Section: Dna Junction Interacting Properties Of Cationic Azacryptandsmentioning
confidence: 99%
“…We decided to perform polyacrylamide gel electrophoresis (PAGE) with the aforementioned candidates along with several control compounds to gain insights into the molecular features that might govern the efficiency of the ligandjunction interactions: two highly selective quadruplex ligands, PNA DOTASQ 26 and AuTMX 2 , 27 known to interact efficiently with non-B DNA structures, π-stacking on accessible guanine assemblies (chiefly the G-quartet), and the "universal" DNA ligand TMPyP4, able to bind to DNA whatever its secondary structures, 23,28 and historically, among the very first reported branched DNA interacting compounds. We decided to perform polyacrylamide gel electrophoresis (PAGE) with the aforementioned candidates along with several control compounds to gain insights into the molecular features that might govern the efficiency of the ligandjunction interactions: two highly selective quadruplex ligands, PNA DOTASQ 26 and AuTMX 2 , 27 known to interact efficiently with non-B DNA structures, π-stacking on accessible guanine assemblies (chiefly the G-quartet), and the "universal" DNA ligand TMPyP4, able to bind to DNA whatever its secondary structures, 23,28 and historically, among the very first reported branched DNA interacting compounds.…”
Section: Emsa Analysis Of the Cationic Azacryptand/junction Assembliesmentioning
confidence: 99%
“…An interesting methodological difference between DSF as applied to nucleic acids is that it typically uses FRET instead of the less specific dye binding phenomenon exploited in proteins, an approach which allows most of the nucleic acid target structure to remain intact and available for the small molecule to bind. Thus, FAM/TAMRA FRET pair has been utilized in T m measurement protocols in search of binders of various structural motifs, including in the context of high-throughput screening [2427]. …”
Section: Experimental Setup and Data Interpretationmentioning
confidence: 99%
“…[20][21][22][23] While the majority of quadruplex DNAbinders reported to date contain planar organic heteroaromatic systems, av ariety of metal complexes (mostly bearing extended planar motifs) were also shown to exhibit large affinities for DNAG -quadruplexes. [29,30] Thea bove arguments prompted us to explore,atamolecular level, the interactions taking place between an organometallic gold(I) NHC compound and ar epresentative DNAG -quadruplex (Tel 23 sequence (5'-TAGGG(TTAGGG) 3 -3')) by ac ombined ESI MS and X-ray diffraction investigative strategy.B ased on recent work, [29] we selected the bis-carbene cationic complex ([Au(9-methylcaffein-8-ylidene) 2 ] + ;F igure 1) for this study, which was earlier reported to be aselective cytotoxic agent in cancer cells.T his compound is able to bind quite strongly to af ew representative G4-DNAs (more selectively than DNA duplexes), as well as 3-and 4-way DNAj unctions. [26,27] However, structural information on adducts formed between metal complexes and G4-DNAi sl imited and would be of great help to develop selective G4 stabilizers.T od ate,c rystal structures have only been reported for adducts of copper(II) and nickel(II) salphen complexes with human telomeric DNA.…”
mentioning
confidence: 99%
“…[12,24,25] An extensive overview of this topic is provided in two recent review articles,where relevant examples are illustrated. [30] Interactions were mainly characterized by spectrofluorimetric methods but thus far no structural data has been obtained for these systems. [28] Additionally,information on the interactions of gold compounds with G4-DNAi se xtremely scarce.…”
mentioning
confidence: 99%